Calorimetric investigation of liquid aluminum-magnesium-zinc alloys - Kim, YB; Sommer, F; Predel, B (ELSEVIER SCIENCE SA LAUSANNE, 1997)
The enthalpy of mixing of liquid Al-Mg-Zn ternary liquid alloys was determined in the temperature range between 883 and 933 K using a high temperature mixing calorimeter. An association model is used to calculate the thermodynamic mixing functions of the ternary alloys based on the thermodynamic properties of the binary bordering systems. The calculated values of the enthalpy of mixing show a good agreement with measured values within the range of experimental accuracy. The presence of additional ternary interactions or ternary associates in the liquid state could not be observed.
Keywords: THERMODYNAMIC FUNCTIONS; ASSOCIATION MODEL; SYSTEM